Genomic and Cellular Integration in the Tripartite Nested Mealybug Symbiosis - Husník, Filip (Jihočeská univerzita, 2017)
The PhD thesis is composed of three publications on genomic, metabolic, and cellular integration between the host and its symbionts in the tripartite nested mealybug system. The articles revealed a path to an intimate endosymbiosis that can be compared to what we think happened before (and to some extent after) bacterial ancestors of key eukaryotic organelles, mitochondria and plastids, became highly integrated into their host cells. I argue that these much younger symbioses may tell us something about how the mitochondria and plastids came to be, at the very least by revealing what types of evolutionary events are possible as stable intracellular relationships proceed along the path of integration.
Genomic and Cellular Integration in the Tripartite Nested Mealybug Symbiosis
Keywords: eukaryogenesis; protein import; endosymbiosis; horizontal gene transfer; eukaryogenesis; protein import; endosymbiosis; horizontal gene transfer